2009
DOI: 10.1007/s11630-009-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of active tip-clearance control through tip cooling injection in an axial turbine cascade

Abstract: This paper presents a numerical investigation of an active tip-clearance control method based on cooling injection from the blade tip surface. It aims to study the influences of air injection on controlling tip clearance flow, with emphasis on the effects of the injection location on secondary flow and the potential thermal benefits from the cooling jet. The results show that injection location plays an important role in the redistribution of secondary flow within the cascade passage. Injection located much cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is somewhat surprising, since both planes 1 and 2 are downstream of the jet injection locations at holes 3 and 4. The vortex still clearly forms, but perhaps the jets divert the leakage flow to a more downstream location, delaying the formation of the vortex, as observed by Niu and Zang [12], and this delay results in lower total pressure drop.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This is somewhat surprising, since both planes 1 and 2 are downstream of the jet injection locations at holes 3 and 4. The vortex still clearly forms, but perhaps the jets divert the leakage flow to a more downstream location, delaying the formation of the vortex, as observed by Niu and Zang [12], and this delay results in lower total pressure drop.…”
Section: Resultsmentioning
confidence: 84%
“…They reported a reduction in total pressure loss, but the jet velocities required appear to be higher than achievable in an engine. Niu and Zang [12] conducted a numerical study of blowing from the tip. They used rows of holes inclined toward the pressure side.…”
Section: Introductionmentioning
confidence: 99%
“…The engine's tip clearance is at its lowest in the accelerated transition state, which makes friction failure easy to happen, according to the literature study [14][15][16]. It is known that the working speed of a typical engine in slow running conditions is approximately 9000RPM based on the relation diagram between time and speed in each typical working condition provided by MTU technical manual and literature [17]. The author equalized the speed in the acceleration process and chose three different speeds within the range of 3000RPM, 6000RPM, and 9000RPM for research.…”
Section: Rotational Speedmentioning
confidence: 99%
“…The tip injection at 81% blade axial chord was most successful in reducing the total pressure deficit in the leakage vortex. Niu and Zang 2527 performed parametric investigations of the tip injection in a high-turning axial turbine cascade, including injection circumferential angle and injection location in the blade-thickness direction. The results showed that, the nearer the injection holes are to the pressure side (PS) corner and the smaller the injection circumferential angle is, the more tip injection can affect the tip leakage flow.…”
Section: Introductionmentioning
confidence: 99%